SIMULASI RELASI DISPERSI KEKISI KRISTAL -Simulation of Dispersion Curve on the Crystal Lattices - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Teknik Etektro dan Teknotogi Informasi Universitas Gadjah Mada, 2000)
ABSTRACT A program for simulation of dispersion curve on the various crystal lattices has been made in Pascal. Many formulations were treated by illustration of an ideal crystal in the harmonic approximation. Simulation had been set along the three-symmetry direction [100], [110], and [111] for each lattice. The results printed out some modes of normal vibrations in w(k) relation from lattices and directions considered. The number of branches from normal modes of vibration is not equaled three for monatomic basis of lattice or six for diatomic basis. The branches could degenerate for some symmetry-direction so that it became the same modes of vibration.